Modular organization of projection neurons in the matrix compartment of the primate striatum - Gimenez-Amaya, JM (J Neurosci, 1991)
It is well known that the striatum has a chemical architecture dividing it into striosomes and matrix, and that these compartments have different input-output connections. However, striatal afferent-fiber systems also form vividly patchy terminal fields in the matrix, and studies in the past year have uncovered instances of nonstriosomal clustering of striatal output neurons. In the experiments reported here, we systematically investigated this output-neuron clustering in the primate, using the striatopallidal system as a model. Our goals were to determine whether the modular organization is a general characteristic of projection neurons in the striatal matrix, whether the modularity occurs independent of striosomal boundaries, and whether the output modules are systematically organized. We studied the distribution of striatopallidal projection neurons in 9 adult squirrel monkeys by centering deposits of the retrograde tracer HRP-WGA in either the external segment or the internal segment of the globus pallidus. Following injections of each type, many retrogradely labeled neurons appeared in the striatal matrix in clusters and bands having cross-sectional diameters of 0.2–0.8 mm. Comparisons with adjoining sections stained to demonstrate striosomes established that the local groups of striatal output neurons sometimes abutted striosomes but often did not. The retrogradely labeled clusters and bands appeared both in the caudate nucleus and in the putamen. Their arrangements were regular and often periodic. These findings suggest that the large matrix compartment of the primate striatum, which is the primary site of origin of striatal outputs to the pallidum and the reticular part of the substantia nigra, contains systematic mosaics of projection neurons. We propose that this output-neuron modularity of the striatal matrix in the primate could serve as the template for redistribution of the massive afferent-fiber systems of the striatum into specialized striatopallidal output channels.